Integrating Micro-Depot Freight Transport in Existing Public Transport Services - Lena Hörsting; Catherine Cleophas (Operations Research Forum, 2023)
As conventional last-mile transport contributes to traffic congestion and pollution, urban areas need new approaches to transporting freight. One promising idea is integrating freight deliveries with existing public transport infrastructures like light rail. However, this concept creates the challenge of offering a high service quality for passengers and freight. In this work, we consider a setting where freight originates from and is transhipped at several public transit stops that serve as micro-depots with a limited storage capacity. Furthermore, the system relies on shared vehicles, where a dedicated share of the capacity can be used to fasten freight containers or as a standing area for passengers. For this setting, we propose an optimisation model that integrates the tactical scheduling of transport services and the allocation of freight containers to those services. To solve realistically sized instances, we propose an adaptive large neighbourhood search heuristic. We use this heuristic to evaluate the system's sensitivity to the capacity of micro-depots and vehicles.
Keywords: 510; Transportation; Logistics; Shared transport; Scheduling; Adaptive large neighbourhood search